Electroslag remelting method of a manganese-copper alloy
Patent Information
- Application Number
- CN202310136283.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-02-20
- Publication Date
- 2026-10-27
- Estimated Expiration
- 2043-02-20
AI Technical Summary
该方法虽然非常新颖,但对设备和工艺要求极高,生产效率低下,不适合大规模推广
[0028](3)本发明采用0.3~0.5的较低填充比,以匹配电渣时高电压、低电流、低熔速的平稳顺利进行。锰铜合金的导热性差,熔速过快则会形成较深的熔池形状,不利于减轻元素偏析和细化凝固组织,而为保持浅平的熔池必然需要高电压、低电流操作。然而,较高电压下,渣池温度必然升高,对于熔点仅为1040~1070℃的锰铜合金来讲,熔速增加是必然的。所以,为避免出现这种情况,只能减少填充比,减少渣金接触面积。Φ300mm结晶器,相同电压(温度)下,每减少0.1的填充比,渣金接触面积就减少20~25%,熔速降低20~25%。
Smart Images

Figure BDA0004085753510000111 
Figure BDA0004085753510000121
Abstract
Description
Technical Field
[0001] This invention belongs to the field of metallurgical technology, specifically relating to an electroslag remelting method for manganese-copper alloys. Background Technology
[0002] Manganese-copper alloy is a high-damping special alloy, generally used in applications or components requiring vibration reduction and noise reduction. Manganese-copper alloy contains numerous elastic twin structures, which undergo relaxation motion under external forces, rapidly dissipating external energy and thus efficiently attenuating mechanical vibrations caused by vibration sources, exhibiting high damping characteristics macroscopically. Currently, due to the complex processing technology of manganese-copper alloy, it is only used in submarine engines, propellers, and fasteners and gears with special vibration reduction requirements.
[0003] Manganese-copper alloys are generally smelted using equipment such as medium-frequency furnaces, vacuum induction furnaces, and electric furnaces. However, due to the high manganese content in the alloy, the alloy has poor thermal conductivity, a long crystallization time, and a coarse microstructure with severe element segregation after solidification. Even after certain heat treatment and deformation processing, the microstructural defects cannot be completely eliminated, which will seriously affect the uniformity of the material properties.
[0004] Publication number CN104911425A discloses a high-manganese-content MnCuNiAlFe five-element damping alloy and its preparation method. This method involves melting the alloy under a protective gas atmosphere of 0.8–1 Pa, followed by high-temperature solution treatment at 700–1200℃ for 1–10 hours after casting the ingot. While this method is relatively simple and has high production efficiency, the 0.8–1 Pa vacuum melting causes significant volatilization of elements such as Mn and Al, making composition control difficult. Furthermore, the solution treatment temperature (1200℃) exceeds the alloy's melting point (approximately 1100℃), failing to eliminate solidification defects. Therefore, this method is not feasible.
[0005] Publication number CN110144472A discloses a vacuum induction melting method for manganese-copper alloys. This method employs a process of "vacuum preheating—argon-protected melting—refining—slag formation—slag removal—alloying—casting" to obtain manganese-copper alloy ingots. The advantage of this process is that the introduction of a slag formation step reduces the inclusion content in the alloy and improves the cleanliness of the metal. This method is also very novel. However, achieving slag removal under vacuum is difficult, as surface slag is hard to completely remove, and the mixing of steel slag can easily cause slag entrapment, re-contaminating the alloy, resulting in more harm than good.
[0006] Publication number CN108559896A discloses a casting method for a high-damping manganese-copper alloy material. This method involves melting in a vacuum induction furnace, followed by direct solidification in a crucible after achieving the required composition. During solidification, a 0-5T transverse static magnetic field is applied at the crystallization interface front to improve macroscopic segregation, promote inclusion flotation, and refine the solidification structure. While this method is novel, it places extremely high demands on equipment and processes, resulting in low production efficiency and making it unsuitable for large-scale implementation.
[0007] Among the publicly available technologies, CN113755729A, CN106148782A, CN113430434A, CN109811167A, etc., have also provided their own methods for preparing manganese-copper alloys. They all have great innovations in terms of process, but consistent with the processes mentioned above, they are either inefficient, complicated to operate, or difficult to guarantee quality, and none of them can meet the needs of industrialization.
[0008] Therefore, it is imperative to develop a reliable and stable manganese-copper alloy smelting process. Summary of the Invention
[0009] This invention discloses an electroslag remelting method for manganese-copper alloys, the purpose of which is to solve the problem of industrialization of manganese-copper alloys.
[0010] To solve the above-mentioned technical problems, the technical solution adopted by the present invention is: an electroslag remelting method for manganese-copper alloy, the electroslag remelting method comprising the following steps:
[0011] (1) Electrode and slag preparation: Baking the CaF2-MgF2-BaF2-CaO-Al2O3 slag system; laying the ingot plate and arc ignition agent; installing the consumable electrode;
[0012] (2) Arc ignition and slag formation: ignite the arc, add slag, adjust the voltage to 25-45V and the current to 2.0-4.0KA, and the slag formation period is 20-30min;
[0013] (3) Remelting: After entering the remelting period, control the voltage at 43-51V, the current at 3500-4500A, and the melting rate at 3.0-3.5kg / min, and replenish the electrode when 20-35kg remains.
[0014] (4) Feeding: During the feeding period, the voltage and current gradually decrease from 43-45V and 3500-4300A to 30-35V and 2000-2500A. The melting ends after the feeding time is 20-25 minutes.
[0015] (5) Demolding: After the mold cools for 30-50 minutes, remove the ingot and cool the electroslag ingot pit to room temperature.
[0016] The chemical composition and mass percentage of the manganese-copper alloy described in this invention are as follows: Mn: 68-71%, Cu: 20-22%, Ni: 4-6%, Mo: 0.5-1.0%, Al: 2.0-2.5%, P≤0.010%, S≤0.010%, with the balance being Fe and unavoidable impurities.
[0017] In step (1) of the present invention, the mass fraction of the CaF2-MgF2-BaF2-CaO-Al2O3 slag system is as follows: CaF2: 15-20%, MgF2: 15-20%, BaF2: 45-60%, CaO: 5-10%, Al2O3: 3-5%, and CaF2 / MgF2 = 1.
[0018] In step (1) of this invention, the baking temperature of the CaF2-MgF2-BaF2-CaO-Al2O3 slag system is 400-450℃, and the baking time is 10-12h.
[0019] In step (1) of the present invention, the hemispherical temperature of the CaF2-MgF2-BaF2-CaO-Al2O3 slag system is 850-900℃.
[0020] The diameter of the manganese-copper alloy consumable electrode of the present invention / the diameter of the electroslag crystallizer is 0.3 to 0.5 (filling ratio).
[0021] The segregation index of any element in the manganese-copper alloy of the present invention is 0.95 to 1.05.
[0022] The segregation index of any element in the manganese-copper alloy of the present invention is 0.96 to 1.04.
[0023] The secondary dendrite spacing of the manganese-copper alloy electroslag ingot described in this invention is 78–122 μm.
[0024] The manganese-copper alloy consumable electrode of this invention has a specification of Φ90-150mm.
[0025] The design concept of this invention is as follows:
[0026] (1) The composition of the manganese-copper alloy of the present invention is 68-71% Mn, 20-22% Cu, 4-6% Ni, 0.5-1.0% Mo, 2.0-2.5% Al, and the balance is Fe. If vacuum furnace smelting or medium frequency furnace melting is used alone, it is difficult to control the solidification structure and element segregation. Therefore, an electroslag process is designed to be added in the subsequent process. The advantages of electroslag metallurgy are used to reduce the content of P, S and inclusions in the alloy, reduce the segregation of elements such as Mn, Cu and Al, and improve the solidification structure.
[0027] (2) The selection of slag system is extremely important for electroslag remelting of manganese-copper alloy. The liquidus temperature of the alloy in this invention is 1040-1070℃. To ensure the electroslag metallurgical effect, the hemispherical point temperature of the slag system should be 860-890℃. At this temperature, commonly used slag systems such as CaF2-CaO, CaF2-Al2O3, and CaF2-CaO-Al2O3 are not suitable for use because their melting points are too high. This invention, through research, discovered that the eutectic point temperature of the slag system of 15-20% CaF2-15-20% MgF2-60-70% BaF2 is 790-820℃. In the molten state, it does not react with elements such as manganese, copper, nickel, molybdenum, and aluminum, exhibiting high chemical stability, and can be used as the main component of the slag system of this invention. To appropriately increase the melting point, enhance desulfurization efficiency, and improve aluminum yield, small amounts of CaO and Al2O3 were added. The final design is CaF2 15-20%, MgF2 15-20%, BaF2 45-60%, CaO 5-10%, Al2O3 3-5%, with CaF2 / MgF2 = 1. Testing showed that the hemispherical point temperature of this slag system is 850-900℃, fully meeting the electroslag remelting requirements of the alloy of this invention.
[0028] (3) This invention employs a relatively low filling ratio of 0.3 to 0.5 to ensure smooth operation under high voltage, low current, and low melting rate during electroslag remelting. Manganese-copper alloys have poor thermal conductivity; excessively high melting rates result in deep molten pools, which are detrimental to reducing elemental segregation and refining the solidification structure. Maintaining a shallow molten pool necessitates high voltage and low current operation. However, at higher voltages, the slag pool temperature inevitably increases. For manganese-copper alloys with a melting point of only 1040–1070℃, an increase in melting rate is inevitable. Therefore, to avoid this situation, the filling ratio must be reduced, thereby decreasing the slag-metal contact area. In a Φ300mm crystallizer, under the same voltage (temperature), a reduction of 0.1 in the filling ratio results in a 20–25% decrease in slag-metal contact area and a 20–25% decrease in melting rate.
[0029] The beneficial effects of adopting the above technical solution are as follows: 1. This invention discloses an electroslag remelting method for manganese-copper alloys. The slag system used is a five-element low-melting-point slag system of CaF2-MgF2-BaF2-CaO-Al2O3 with a hemispherical point temperature of 850-900℃, which matches the relatively low liquidus temperature of manganese-copper alloys. High voltage, low current, and low melting rate are used during electroslag remelting to obtain good surface quality and uniform solidification structure. 2. To ensure the smooth progress of the electroslag process at low melting rates, this invention uses a slag filling ratio of 0.3-0.5. The manganese-copper alloy electroslag ingots smelted by this method have a smooth surface without slag grooves, a uniform solidification structure, a secondary dendrite spacing of 78-122μm, and macroscopic segregation indices of major elements such as Mn, Cu, and Al of 0.95-1.05, fully meeting the requirements of subsequent hot working. Detailed Implementation
[0030] The present invention will be further described in detail below with reference to specific embodiments.
[0031] Example 1
[0032] The specific process for this electroslag manganese-copper alloy is as follows.
[0033] (1) Electrode and slag preparation:
[0034] The consumable electrode of Example 1 was ground and welded to the dummy electrode with a filling ratio (diameter of manganese-copper alloy consumable electrode / diameter of electroslag crystallizer) of 0.33. The chemical composition is shown in Table 1 (the chemical composition of the electrode and the electroslag ingot is consistent). 22 kg of CaF2-MgF2-BaF2-CaO-Al2O3 slag material was baked in a furnace at 420℃ for 10 h. The composition was: CaF2: 20%, MgF2: 20%, BaF2: 47%, CaO: 10%, Al2O3: 3%, and the hemispherical point temperature of the slag system was 850℃.
[0035] Furnace loading: A steel ingot plate with a diameter of Φ200mm and a thickness of 30mm is laid in the center of the bottom water tank. Then, an arc-starting iron ring with a diameter of Φ180mm, a height of 50mm, and a thickness of 0.1mm is placed on the ingot plate. 300g of manganese-copper alloy arc-starting chips and 50g of fully baked CaF2 powder are placed inside the ring. Then, a Φ300×1400mm crystallizer, a gas protection hood, and a consumable electrode are installed in sequence. The trolley is driven into the melting position, and the cooling water, argon, and flue gas pipelines are connected.
[0036] Argon purging: Argon gas is introduced into the furnace at a flow rate of 120 L / min until the oxygen content in the gas protective hood is ≤0.005%. The argon gas flow rate is then adjusted to 30-50 L / min. During the subsequent melting process, the oxygen content in the protective hood is ensured to be ≤0.01%.
[0037] (2) Arc ignition and slag formation: Lower the electrode to 20mm from the arc igniter, set the voltage to 25V and the current to 2.3KA, ignite the arc, and slowly add the slag material within 10 minutes after the arc stabilizes. The slag formation period is 25 minutes, during which the power is slowly increased, eventually reaching a current of 3700A and a voltage of 45V.
[0038] (3) Remelting: During the remelting period, adjust the voltage to 45V~48V and the current to 3700A~4300A, and ensure the melting rate is 3.2±0.1kg / min during the smelting process. The remelting period ends at 45V and 4000A.
[0039] (4) Compensation: The initial weight for compensation is 30kg, and the compensation time is 23min. During compensation, the voltage and current are slowly reduced from 45V and 4000A at the beginning of compensation to 31V and 2300A at the end.
[0040] (5) Demolding: Demolding is performed 40 minutes after the end of smelting. The electroslag steel ingot is cooled to room temperature to obtain manganese-copper alloy electroslag steel ingot.
[0041] Samples were taken from the top of the electroslag ingot. The main chemical components measured at the center were: Mn: 69.1%, Cu: 21.5%, Ni: 5.44%, Mo: 0.78%, Al: 2.01%, P: 0.008%, S: 0.004%, Fe: 1.16%; the main chemical components measured at the edge were: Mn: 70.0%, Cu: 20.7%, Ni: 5.34%, Mo: 0.80%, Al: 2.01%. The composition is 0.00%, P: 0.010%, S: 0.005%, Fe: 1.14%; the central element segregation index is Mn: 0.99, Cu: 1.02, Ni: 1.01, Mo: 0.98, Al: 1.01, Fe: 1.01; the edge element segregation index is Mn: 1.01, Cu: 0.98, Ni: 0.99, Mo: 1.02, Al: 0.99, Fe: 0.99. The central secondary dendrite spacing is 119 μm, at 1 / 2R it is 103 μm, and at the edge it is 82 μm. The composition and solidification structure are uniform, the surface is smooth, and subsequent hot working deformation is easy without cracking.
[0042] Example 2
[0043] The specific process for this electroslag manganese-copper alloy is as follows.
[0044] (1) Electrode and slag preparation:
[0045] The consumable electrode from Example 2 in Table 1 was polished and welded onto the dummy electrode with a filling ratio of 0.4. The chemical composition is shown in Table 1. 24 kg of CaF2-MgF2-BaF2-CaO-Al2O3 slag was baked in a furnace at 440℃ for 12 h. The composition was: CaF2: 18%, MgF2: 18%, BaF2: 52%, CaO: 8%, Al2O3: 4%, and the hemispherical temperature of the slag system was 870℃.
[0046] Furnace loading: A steel ingot plate with a diameter of Φ220mm and a thickness of 30mm is laid in the center of the bottom water tank. Then, an arc-starting iron ring with a diameter of Φ200mm, a height of 50mm, and a thickness of 0.1mm is placed on the ingot plate. 330g of manganese-copper alloy arc-starting chips and 60g of fully baked CaF2 powder are placed inside the ring. Then, a Φ300×1400mm crystallizer, a gas protection hood, and a consumable electrode are installed in sequence. The trolley is driven into the melting position, and the cooling water, argon, and flue gas pipelines are connected.
[0047] Argon purging: Argon gas is introduced into the furnace at a flow rate of 150 L / min until the oxygen content in the gas protective hood is ≤0.005%. The argon gas flow rate is then adjusted to 30-50 L / min. During the subsequent melting process, the oxygen content in the protective hood is ensured to be ≤0.01%.
[0048] (2) Arc ignition and slag formation: Lower the electrode to 25mm from the arc igniter, set the voltage to 27V and the current to 2.4KA, ignite the arc, and slowly add the slag material within 12 minutes after the arc stabilizes. The slag formation period is 27 minutes, during which the power is slowly increased, eventually reaching a current of 3800A and a voltage of 43V.
[0049] (3) Remelting: During the remelting period, adjust the voltage to 43V~48V and the current to 3800A~4300A, and ensure the melting rate is 3.2±0.1kg / min during the smelting process. The remelting period ends at 43V and 3800A.
[0050] (4) Compensation: The initial weight for compensation is 32kg, and the compensation time is 22min. During compensation, the voltage and current are slowly reduced from 43V and 3800A at the beginning of compensation to 30V and 2200A at the end.
[0051] (5) Demolding: Demolding is performed 45 minutes after the end of smelting, and the electroslag steel ingot is cooled to room temperature.
[0052] Samples were taken from the top of the electroslag ingot. The main chemical components measured at the center were: Mn: 69.4%, Cu: 21.3%, Ni: 5.84%, Mo: 0.50%, Al: 2.29%, P: 0.006%, S: 0.005%, Fe: 0.66%; the main chemical components measured at the edge were: Mn: 68.4%, Cu: 22.1%, Ni: 5.96%, Mo: 0.53%, Al: 2.26%. The composition is as follows: P: 0.008%, S: 0.003%, Fe: 0.74%; the composition meets the standards. The central elemental segregation index is Mn: 1.02, Cu: 0.98, Ni: 0.99, Mo: 0.97, Al: 1.01, Fe: 0.96; the edge elemental segregation index is Mn: 0.98, Cu: 1.02, Ni: 1.01, Mo: 1.03, Al: 0.99, Fe: 1.04. The central secondary dendrite spacing is 120 μm, 99 μm at 1 / 2R, and 81 μm at the edge. The composition and solidification structure are uniform, the surface is smooth, and subsequent hot working deformation is easy without cracking.
[0053] Example 3
[0054] The specific process for this electroslag manganese-copper alloy is as follows.
[0055] (1) Electrode and slag preparation:
[0056] The consumable electrode of Example 3 was polished and welded onto the dummy electrode with a filling ratio of 0.5. The chemical composition is shown in Table 1. 25 kg of CaF2-MgF2-BaF2-CaO-Al2O3 slag was baked in a furnace at 450℃ for 12 h. The composition was: CaF2: 15%, MgF2: 15%, BaF2: 60%, CaO: 6%, Al2O3: 4%, and the hemispherical point temperature of the slag system was 900℃.
[0057] Furnace loading: A steel ingot plate with a diameter of Φ230mm and a thickness of 30mm is laid in the center of the bottom water tank. Then, an arc-starting iron ring with a diameter of Φ210mm, a height of 50mm, and a thickness of 0.1mm is placed on the ingot plate. 400g of manganese-copper alloy arc-starting chips and 65g of fully baked CaF2 powder are placed inside the ring. Then, a Φ300×1400mm crystallizer, a gas protection hood, and a consumable electrode are installed in sequence. The trolley is driven into the melting position, and the cooling water, argon, and flue gas pipelines are connected.
[0058] Argon purging: Argon gas is introduced into the furnace at a flow rate of 150 L / min until the oxygen content in the gas protective hood is ≤0.005%. The argon gas flow rate is then adjusted to 30-50 L / min. During the subsequent melting process, the oxygen content in the protective hood is ensured to be ≤0.01%.
[0059] (2) Arc ignition and slag formation: Lower the electrode to 30mm from the arc igniter, set the voltage to 30V and the current to 2.5KA, ignite the arc, and slowly add the slag material within 15 minutes after the arc stabilizes. The slag formation period is 30 minutes, during which the power is slowly increased, eventually reaching a current of 4000A and a voltage of 45V.
[0060] (3) Remelting: During the remelting period, adjust the voltage to 45V~51V and the current to 4000A~4500A, and ensure the melting rate is 3.4±0.1kg / min during the smelting process. The remelting period ends at 45V and 4300A.
[0061] (4) Compensation: The initial weight for compensation is 35kg, and the compensation time is 25min. During compensation, the voltage and current are slowly reduced from 45V and 4300A at the beginning of compensation to 35V and 2500A at the end.
[0062] (5) Demolding: Demolding is performed 50 minutes after the end of smelting, and the electroslag steel ingot is cooled to room temperature.
[0063] Samples were taken from the top of the electroslag ingot. The main chemical components measured at the center were: Mn: 70.0%, Cu: 20.3%, Ni: 5.17%, Mo: 0.63%, Al: 2.10%, P: 0.006%, S: 0.005%, Fe: 1.79%; the main chemical components measured at the edge were: Mn: 69.4%, Cu: 21.1%, Ni: 5.22%, Mo: 0.59%, Al: 2.12%. P: 0.008%, S: 0.006%, Fe: 1.56%; composition meets standards. Central element segregation indices: Mn: 1.01, Cu: 0.96, Ni: 0.96, Mo: 1.02, Al: 0.99, Fe: 1.04; Edge element segregation indices: Mn: 0.99, Cu: 1.04, Ni: 1.04, Mo: 0.98, Al: 1.01, Fe: 0.96. The central secondary dendrite spacing is 122 μm, at 1 / 2R it is 104 μm, and at the edge it is 85 μm. The composition and solidification structure are uniform, the surface is smooth, and subsequent hot working deformation is easy without cracking.
[0064] Example 4
[0065] The specific process for this electroslag manganese-copper alloy is as follows.
[0066] (1) Electrode and slag preparation:
[0067] The consumable electrode from Example 4 in Table 1 was polished and welded onto the dummy electrode with a filling ratio of 0.4. The chemical composition is shown in Table 1. 24 kg of CaF2-MgF2-BaF2-CaO-Al2O3 slag was baked in a furnace at 440℃ for 12 h. The composition was: CaF2: 16%, MgF2: 16%, BaF2: 58%, CaO: 5%, Al2O3: 5%, and the hemispherical temperature of the slag system was 880℃.
[0068] Furnace loading: A steel ingot plate with a diameter of Φ220mm and a thickness of 30mm is laid in the center of the bottom water tank. Then, an arc-starting iron ring with a diameter of Φ200mm, a height of 50mm, and a thickness of 0.1mm is placed on the ingot plate. 330g of manganese-copper alloy arc-starting chips and 60g of fully baked CaF2 powder are placed inside the ring. Then, a Φ300×1400mm crystallizer, a gas protection hood, and a consumable electrode are installed in sequence. The trolley is driven into the melting position, and the cooling water, argon, and flue gas pipelines are connected.
[0069] Argon purging: Argon gas is introduced into the furnace at a flow rate of 150 L / min until the oxygen content in the gas protective hood is ≤0.005%. The argon gas flow rate is then adjusted to 30-50 L / min. During the subsequent melting process, the oxygen content in the protective hood is ensured to be ≤0.01%.
[0070] (2) Arc ignition and slag formation: Lower the electrode to 25mm from the arc igniter, set the voltage to 27V and the current to 2.4KA, ignite the arc, and slowly add the slag material within 12 minutes after the arc stabilizes. The slag formation period is 27 minutes, during which the power is slowly increased, eventually reaching a current of 3800A and a voltage of 44V.
[0071] (3) Remelting: During the remelting period, adjust the voltage to 44V~48V and the current to 3800A~4300A, and ensure the melting rate is 3.3±0.1kg / min during the smelting process. The remelting period ends at 44V and 3800A.
[0072] (4) Compensation: The initial weight for compensation is 32kg, and the compensation time is 22min. During compensation, the voltage and current are slowly reduced from 44V and 3800A at the beginning of compensation to 30V and 2200A at the end.
[0073] (5) Demolding: Demolding is performed 45 minutes after the end of smelting, and the electroslag steel ingot is cooled to room temperature.
[0074] Samples were taken from the top of the electroslag ingot. The main chemical components measured at the center were: Mn: 69.5%, Cu: 21.2%, Ni: 4.44%, Mo: 1.00%, Al: 2.42%, P: 0.006%, S: 0.003%, Fe: 1.43%; the main chemical components measured at the edge were: Mn: 70.1%, Cu: 20.8%, Ni: 4.51%, Mo: 0.97%, Al: 2.36%. P: 0.008%, S: 0.004%, Fe: 1.25%; composition meets standards. Central element segregation indices: Mn: 0.97, Cu: 1.03, Ni: 0.98, Mo: 1.01, Al: 1.01, Fe: 1.02; Edge element segregation indices: Mn: 1.03, Cu: 0.97, Ni: 1.02, Mo: 0.99, Al: 0.99, Fe: 0.98. The central secondary dendrite spacing is 116 μm, 95 μm at 1 / 2R, and 84 μm at the edges. The composition and solidification structure are uniform, the surface is smooth, and subsequent hot working deformation is easy without cracking.
[0075] Example 5
[0076] The specific process for this electroslag manganese-copper alloy is as follows.
[0077] (1) Electrode and slag preparation:
[0078] The consumable electrode of Example 5 was polished and welded onto the dummy electrode with a filling ratio of 0.3. The chemical composition is shown in Table 1. 20 kg of CaF2-MgF2-BaF2-CaO-Al2O3 slag was baked in a furnace at 400℃ for 10 h. The composition was: CaF2: 17%, MgF2: 17%, BaF2: 55%, CaO: 6%, Al2O3: 5%, and the hemispherical point temperature of the slag system was 890℃.
[0079] Furnace loading: A steel ingot plate with a diameter of Φ180mm and a thickness of 30mm is laid in the center of the bottom water tank. Then, an arc-starting iron ring with a diameter of Φ150mm, a height of 50mm, and a thickness of 0.1mm is placed on the ingot plate. 200g of manganese-copper alloy arc-starting chips and 40g of fully baked CaF2 powder are placed inside the ring. Then, a Φ300×1400mm crystallizer, a gas protection hood, and a consumable electrode are installed in sequence. The trolley is driven into the melting position, and the cooling water, argon, and flue gas pipelines are connected.
[0080] Argon purging: Argon gas is introduced into the furnace at a flow rate of 100 L / min until the oxygen content in the gas protective hood is ≤0.005%. The argon gas flow rate is then adjusted to 30-50 L / min. During the subsequent melting process, the oxygen content in the protective hood is ensured to be ≤0.01%.
[0081] (2) Arc ignition and slag formation: Lower the electrode to 18mm from the arc igniter, set the voltage to 25V and the current to 2KA, ignite the arc, and slowly add the slag material within 8 minutes after the arc stabilizes. The slag formation period is 20 minutes, during which the power is slowly increased, eventually reaching a current of 3500A and a voltage of 43V.
[0082] (3) Remelting: During the remelting period, adjust the voltage to 43V~46V and the current to 3500A~4000A, and ensure the melting rate is 3.1±0.1kg / min during the smelting process. The remelting period ends at 43V and 3500A.
[0083] (4) Compensation: The initial weight for compensation is 20kg, and the compensation time is 20min. During compensation, the voltage and current are slowly reduced from 43V and 3500A at the beginning of compensation to 30V and 2000A at the end.
[0084] (5) Demolding: Demolding is performed 30 minutes after the end of smelting, and the electroslag steel ingot is cooled to room temperature.
[0085] Samples were taken from the top of the electroslag ingot. The main chemical components measured at the center were: Mn: 70.9%, Cu: 20.0%, Ni: 4.11%, Mo: 0.73%, Al: 2.32%, P: 0.005%, S: 0.004%, Fe: 1.93%; the main chemical components measured at the edge were: Mn: 70.4%, Cu: 20.2%, Ni: 4.16%, Mo: 0.75%, Al: 2.31%. P: 0.006%, S: 0.006%, Fe: 2.06%; composition meets standards. Central element segregation indices: Mn: 0.98, Cu: 1.02, Ni: 1.01, Mo: 1.01, Al: 1.01, Fe: 1.02; Edge element segregation indices: Mn: 1.02, Cu: 0.98, Ni: 0.99, Mo: 0.99, Al: 0.99, Fe: 0.98. The central secondary dendrite spacing is 108 μm, at 1 / 2R it is 89 μm, and at the edge it is 78 μm. The composition and solidification structure are uniform, the surface is smooth, and subsequent hot working deformation is easy without cracking.
[0086] Example 6
[0087] The specific process for this electroslag manganese-copper alloy is as follows.
[0088] (1) Electrode and slag preparation:
[0089] The consumable electrode of Example 6 was polished and welded onto the dummy electrode with a filling ratio of 0.47. The chemical composition is shown in Table 1. 25 kg of CaF2-MgF2-BaF2-CaO-Al2O3 slag was baked in a furnace at 450℃ for 12 h. The composition was: CaF2: 20%, MgF2: 20%, BaF2: 45%, CaO: 10%, Al2O3: 5%, and the hemispherical temperature of the slag system was 855℃.
[0090] Furnace loading: A steel ingot plate with a diameter of Φ240mm and a thickness of 30mm is laid in the center of the bottom water tank. Then, an arc-starting iron ring with a diameter of Φ220mm, a height of 50mm, and a thickness of 0.1mm is placed on the ingot plate. 400g of manganese-copper alloy arc-starting chips and 60g of fully baked CaF2 powder are placed inside the ring. Then, a Φ300×1400mm crystallizer, a gas protection hood, and a consumable electrode are installed in sequence. The trolley is driven into the melting position, and the cooling water, argon, and flue gas pipelines are connected.
[0091] Argon purging: Argon gas is introduced into the furnace at a flow rate of 150 L / min until the oxygen content in the gas protective hood is ≤0.005%. The argon gas flow rate is then adjusted to 30-50 L / min. During the subsequent melting process, the oxygen content in the protective hood is ensured to be ≤0.01%.
[0092] (2) Arc ignition and slag formation: Lower the electrode to 25mm from the arc igniter, set the voltage to 30V and the current to 2.8KA, ignite the arc, and slowly add the slag material within 13 minutes after the arc stabilizes. The slag formation period is 28 minutes, during which the power is slowly increased, eventually reaching a current of 3900A and a voltage of 45V.
[0093] (3) Remelting: During the remelting period, adjust the voltage to 45V~48V and the current to 3900A~4400A, and ensure the melting rate is 3.3±0.1kg / min during the smelting process. The remelting period ends at 45V and 3900A.
[0094] (4) Compensation: The initial weight for compensation is 32kg, and the compensation time is 25min. During compensation, the voltage and current are slowly reduced from 45V and 3900A at the beginning of compensation to 30V and 2300A at the end.
[0095] (5) Demolding: Demolding is performed 45 minutes after the end of smelting, and the electroslag steel ingot is cooled to room temperature.
[0096] Samples were taken from the top of the electroslag ingot. The main chemical components measured at the center were: Mn: 70.1%, Cu: 21.3%, Ni: 4.00%, Mo: 0.80%, Al: 2.21%, P: 0.005%, S: 0.006%, Fe: 1.58%; the main chemical components measured at the edge were: Mn: 70.2%, Cu: 20.9%, Ni: 4.06%, Mo: 0.79%, Al: 2.25%. P: 0.006%, S: 0.002%, Fe: 1.54%; composition meets standards. Central element segregation indices: Mn: 1.01, Cu: 0.99, Ni: 0.99, Mo: 0.97, Al: 1.01, Fe: 0.98; Edge element segregation indices: Mn: 0.99, Cu: 1.01, Ni: 1.01, Mo: 1.03, Al: 0.99, Fe: 1.02. Central secondary dendrite spacing is 121 μm, at 1 / 2R it is 106 μm, and at the edges it is 88 μm. The composition and solidification structure are uniform, the surface is smooth, and subsequent hot working deformation is easy without cracking.
[0097] Table 1. Composition (wt%) and specifications of manganese-copper alloy consumable electrodes in Examples 1-6
[0098]
[0099]
[0100] The above description is merely a preferred embodiment of the present invention and should not be construed as limiting the scope of the invention. Although the present invention has been described in detail with reference to the foregoing embodiments, those skilled in the art can still modify the technical solutions described in the foregoing embodiments or make equivalent substitutions for some of the technical features. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention are all within the scope of the present invention.
Claims
1. A method for electroslag remelting of a manganese-copper alloy, characterized in that: The electroslag remelting method includes the following steps: (1) Electrode and slag preparation: Baking CaF2-MgF2-BaF2-CaO-Al2O3 slag system; laying ingot plate and arc ignition agent; installing consumable electrode; The mass fraction of the CaF2-MgF2-BaF2-CaO-Al2O3 slag system is as follows: CaF2: 15-20%, MgF2: 15-20%, BaF2: 45-60%, CaO: 5-10%, Al2O3: 3-5%, and CaF2 / MgF2 = 1. (2) Arc ignition and slag formation: ignite the arc, add slag, adjust the voltage to 25-45V and the current to 2.0-4.0KA, and the slag formation period is 20-30min; (3) Remelting: After entering the remelting period, control the voltage to 43-51V, the current to 3500-4500A, and the melting rate to 3.0-3.5kg / min, and replenish the electrode when 20-35kg remains. (4) Feeding: During the feeding period, the voltage and current gradually decrease from 43-45V and 3500-4300A to 30-35V and 2000-2500A, and the melting ends after feeding for 20-25 minutes; (5) Demolding: After the mold has cooled for 30-50 minutes, the ingot is removed and the electroslag ingot pit is cooled to room temperature.
2. The electroslag remelting method for a manganese-copper alloy according to claim 1, characterized in that: The chemical composition and mass percentage of the manganese-copper alloy are as follows: Mn: 68-71%, Cu: 20-22%, Ni: 4-6%, Mo: 0.5-1.0%, Al: 2.0-2.5%, P≤0.010%, S≤0.010%, with the balance being Fe and unavoidable impurities.
3. The electroslag remelting method for a manganese-copper alloy according to claim 1 or 2, characterized in that: In step (1), the baking temperature of the CaF2-MgF2-BaF2-CaO-Al2O3 slag system is 400-450℃, and the baking time is 10-12h.
4. The electroslag remelting method for a manganese-copper alloy according to claim 1 or 2, characterized in that: The hemispherical temperature of the CaF2-MgF2-BaF2-CaO-Al2O3 slag system in step (1) is 850-900℃.
5. The electroslag remelting method for a manganese-copper alloy according to claim 1 or 2, characterized in that: The diameter of the manganese-copper alloy consumable electrode / the diameter of the electroslag crystallizer is 0.3 to 0.
5.
6. The electroslag remelting method for a manganese-copper alloy according to claim 1 or 2, characterized in that: The segregation index of any element in the manganese-copper alloy is 0.95 to 1.
05.
7. The electroslag remelting method for a manganese-copper alloy according to claim 1 or 2, characterized in that: The segregation index of any element in the manganese-copper alloy is 0.96 to 1.
04.
8. The electroslag remelting method for a manganese-copper alloy according to claim 1 or 2, characterized in that: The secondary dendrite spacing of the manganese-copper alloy electroslag ingot is 78–122 μm.
9. The electroslag remelting method for a manganese-copper alloy according to claim 1 or 2, characterized in that: The manganese-copper alloy consumable electrode has a specification of Φ90-150mm.
Citation Information
Patent Citations
High manganese content manganese (Mn) copper (Cu) nickel (Ni) aluminum (Al) iron (Fe) quinary damping alloy and a preparation method thereof
CN104911425A
Method for melting manganese-copper alloy through vacuum induction furnace
CN106148782A
Material for casting high damping manganese copper alloy and manufacturing method thereof
CN108559896A
Method for industrially producing manganese-copper alloy
CN109811167A
Vacuum induction smelting method for manganese-copper damping alloy
CN110144472A